Метод розрахунку довговічності черв'ячної передачі з архімедовим черв'яком - Чернець, М.В. (Видавничий дім "Академперіодика" НАН України, 2008)
On the basis of the well-known mathematical model of materials wear under sliding friction, a method to study the wear kinetics of Archimedean worm gears and to calculate their resource is developed. A numerical solution of the problem is given.